2021
DOI: 10.1021/acschemneuro.1c00348
|View full text |Cite
|
Sign up to set email alerts
|

NNL-3: A Synthetic Intermediate or a New Class of Hydroxybenzotriazole Esters with Cannabinoid Receptor Activity?

Abstract: Synthetic cannabinoid receptor agonists (SCRAs) remain a prolific class of new psychoactive substances (NPS) and continue to expand rapidly. Despite the recent identification of hydroxybenzotriazole (HOBt) containing SCRAs in synthetic cannabis samples, there is currently no information regarding the pharmacological profile of these NPS with respect to human CB1 and CB2 receptors. In the current study, a series consisting of seven HOBt indole-, indazole-, and 7-azaindole-carboxylates bearing a range of N-alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…In vitro cannabinoid functional activity was determined using a fluorescence-based membrane potential assay in stably transfected AtT20 cells expressing human CB 1 or CB 2 receptors, with receptor activation normalized to 1 μM CP55,940. ,,, Several of the functional activity measurements could not be determined due to insufficient activation at the maximum concentration (see Table ). For compounds with a determinable EC 50 , the same trends were observed in their functional activity as in their binding affinity.…”
Section: Resultssupporting
confidence: 80%
“…In vitro cannabinoid functional activity was determined using a fluorescence-based membrane potential assay in stably transfected AtT20 cells expressing human CB 1 or CB 2 receptors, with receptor activation normalized to 1 μM CP55,940. ,,, Several of the functional activity measurements could not be determined due to insufficient activation at the maximum concentration (see Table ). For compounds with a determinable EC 50 , the same trends were observed in their functional activity as in their binding affinity.…”
Section: Resultssupporting
confidence: 80%
“…Looking at other SCRAs, however, this is not a consistent finding. For instance, comparing the CB 1 activity of the assumed SCRA intermediate NNL‐3 (HOBt‐5F‐P7AIC, carrying a fluoro pentyl tail), with its defluorinated (HOBt‐P7AIC) or its cyclohexyl methyl (HOBt‐CHM7AIC) analog, we noticed a dramatic decrease in activity for the HOBt‐CHM7AIC, whereas both pentyl analogs had a quite similar activation profile 61 . Furthermore, when comparing two L‐valine SCRAs at CB 1 , replacement of the fluoro pentyl tail in 5F‐AB‐PINACA (EC 50 = 55.4 nM) by a cyclohexyl methyl moiety in AB‐CHMINACA (EC 50 = 3.45 nM) did yield a more potent compound, whereas the tert ‐leucine analogs 5F‐MDMB‐PINACA (EC 50 = 0.84 nM) and MDMB‐CHMINACA (EC 50 = 0.78 nM) had essentially the same potency at CB 1.…”
Section: Resultsmentioning
confidence: 99%
“…A methyl group at the 3-or 5-position of the piperazine ring is reported to improve potency, 62 and our previous work has also shown that SCRAs that interact with these two residues may give rise to stronger binding affinity to the receptor. 63 The IFD score, which indicates binding affinity, shows that Org 28611 has a stronger binding affinity to both the CB 1 receptors compared to compound 7 (−9744.10 and −9726.62 kcal/mol, respectively). 2) are more critical for determining whether a compound acts on Ca V 3, CBRs, or both.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…All Ca V 3.x experiments were performed using HEK293 FlpIn T-Rex cells stably transfected with pcDNA5 constructs encoding human Ca V 3.x cDNA. 63 Ca V 3.x expression was induced 24 h before membrane potential assays or electrophysiology experiments by adding 2 μg/mL tetracycline. Human CB 1 or CB 2 was stably transfected into AtT-20 FlpIn and maintained using 80 μg/mL hygromycin within the culture media.…”
Section: ■ Methodsmentioning
confidence: 99%